Surgical Experience of Video-Assisted Mediastinoscopy for Nonlung Cancer Diseases - Yazgan, Serkan; Ucvet, Ahmet; Gursoy, Soner; Ceylan, Kenan Can; Yıldırım, Şener (The Thoracic and Cardiovascular Surgeon, 2020)
Background Video-assisted mediastinoscopy (VAM) is a valuable method in the investigation of diseases with mediastinal lymphadenopathy or those localized in the mediastinum. The aim of this study was to determine the diagnostic value of VAM in the investigation of mediastinal involvement of nonlung cancer diseases and to describe our institutional surgical experience.Methods Clinical parameters such as age, sex, histological diagnosis, morbidity, and mortality of all patients who underwent VAM for the investigation of mediastinal involvement of diseases except lung cancer between January 2006 and July 2018 were retrospectively reviewed, and the diagnostic efficacy of VAM was determined statistically.Results During the study period, 388 patients underwent VAM, and 536 lymph nodes were sampled for histopathological evaluation of mediastinum due to mediastinal lymphadenopathy or paratracheal lesions. The most common diagnoses were sarcoidosis (n = 178 [45.9%]), tuberculous lymphadenitis (n = 108 [27.8%]), lymphadenitis with anthracosis (n = 72 [18.6%]), and lymphoma (n = 15 [3.9%]).Conclusion The results of the study show that VAM should be used because of its high diagnostic benefit in mediastinal lymphadenopathies, which are difficult to diagnose, or mediastinal lesions located in the paratracheal region. Despite the increase in the number of new diagnostic modalities, VAM is still the most effective method and a gold standard.
Keywords: mediastinum; tuberculosis; outcomes